Cytokine profiling in chagas disease: towards understanding the association with infecting Trypanosoma cruzi discrete typing units (a benefit trial sub-study) (2014)
Background Chagas disease caused by the protozoan Trypanosoma cruzi is an important public health problem in Latin America. The immunological mechanisms involved in Chagas disease pathogenesis remain incompletely elucidated. The aim of this study was to explore cytokine profiles and their possible association to the infecting DTU and the pathogenesis of Chagas disease. Methods 109 sero-positive T. cruzi patients and 21 negative controls from Bolivia and Colombia, were included. Flow cytometry assays for 13 cytokines were conducted on human sera. Patients were divided into two groups: in one we compared the quantification of cytokines between patients with and without chronic cardiomyopathy; in second group we compared the levels of cytokines and the genetic variability of T. cruzi. Results Significant difference in anti-inflammatory and pro-inflammatory cytokines profiles was observed between the two groups cardiac and non-cardiac. Moreover, serum levels of IFN-?, IL-12, IL-22 and IL-10 presented an association with the genetic variability of T.cruzi, with significant differences in TcI and mixed infections TcI/TcII. Conclusion Expression of anti-inflammatory and pro-inflammatory cytokines may play a relevant role in determining the clinical presentation of chronic patients with Chagas disease and suggests the occurrence of specific immune responses, probably associated to different T. cruzi DTUs.